Empowering Persons with Intellectual Disabilities Through Work/School Alternation: a Positive Case study - Emanuela Zappella (Journal of Child and Adolescent Psychiatry, 2019)
Entry into the world of work is an important moment for people with disabilities and for their professional inclusion. Using a case study, This research presents the project of school/work alternation carried out with a student with intellectual disability within a supermarket during the frequency of the last year in a higher institute in northern Italy. This study intends to describe the process and highlight the strategies used in this experience. The paper ends with an analysis of the factors that can favour a positive experience and which can be a starting-point for other, similar experiences. This experience shows that, with adequate training, people with intellectual disabilities can be protagonists of an experience that favors their well-being and social inclusion.
Keywords: life project